2003
DOI: 10.1094/phyto.2003.93.12.1505
|View full text |Cite
|
Sign up to set email alerts
|

Osmotin and Thaumatin from Grape: A Putative General Defense Mechanism Against Pathogenic Fungi

Abstract: Little information is available concerning the expression of pathogenesis-related (PR) proteins in grapevine (Vitis vinifera) and their effect properties on the major fungal pathogens of grape. A systematic study was performed on the effect of total or individual grape proteins on mycelial growth, spore germination, and germ tube growth of Uncinula necator, Phomopsis viticola, and Botrytis cinerea. Two proteins, identified as PR proteins by immunological methods and by N-terminal sequencing as osmotin and thau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…Members of the PR-1, and the thaumatin-like PR-5 families have been associated with activity against oomycetes. PR-5-type proteins are thought to create trans-membrane pores and exhibit antifungal activities in vitro by blocking spore germination and germ tube growth of Uncinula necator, Phomopsis viticola and Botrytis cinerea (Monteiro et al 2003). Interestingly, we found PR-1 to be induced as early as 12 hpi whereas PR-5 showed no induction over the 48 h time course after inoculation with P. viticola.…”
Section: Defence-related Genesmentioning
confidence: 57%
“…Members of the PR-1, and the thaumatin-like PR-5 families have been associated with activity against oomycetes. PR-5-type proteins are thought to create trans-membrane pores and exhibit antifungal activities in vitro by blocking spore germination and germ tube growth of Uncinula necator, Phomopsis viticola and Botrytis cinerea (Monteiro et al 2003). Interestingly, we found PR-1 to be induced as early as 12 hpi whereas PR-5 showed no induction over the 48 h time course after inoculation with P. viticola.…”
Section: Defence-related Genesmentioning
confidence: 57%
“…The isolation and characterization of osmotin and osmotin-like genes from grapes (Monteiro et al 2003), pepper (Hong et al 2004), soybean (Onishi et al 2006), black night shade (Jami et al 2007) and strawberry (Wu et al 2001;Zhang and Shih 2007) has been reported. Osmotin and osmotin-like proteins can also be activated by microbial infections and by various abiotic stresses (Velazhahan et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thaumatin-like proteins display antifungal activity in vitro against a wide variety of pathogens (Krebitz et al, 2003;Van Loon & Van Strien, 1999), and enhance fungal resistance when overexpressed in transgenic plants (Campbell et al, 2002;Velazhahan & Muthukrishnan, 2003). However, there are no reports of direct implication of PR-5 proteins in major gene resistance, and these are more likely to be generalized secondary effectors (Martin et al, 2003;Monteiro et al, 2003). Benko-Iseppon et al (2003) recently identified PR-5-like sequences in the vicinity of a fusarium wilt-resistance locus in chickpea (Cicer arietinum), but they hypothesized that this reflects nonrandom localization of genes encoding pathogenesis-related proteins such as PR-5 with disease-resistance proteins, as has been observed in Arabidopsis (Benko-Iseppon et al, 2003).…”
Section: Disease-resistance Candidate Genesmentioning
confidence: 99%